Preconfigured patterns are the primary driver of offline multi‐neuronal sequence replay. Issue 3 (22nd November 2018) - Liu, Kefei; Sibille, Jeremie; Dragoi, George
Abstract: Spontaneous neuronal ensemble activity in the hippocampus is believed to result from a combination of preconfigured internally generated dynamics and the unique patterns of activity driven by recent experience. Previous research has established that preconfigured sequential neuronal patterns (i.e., preplay) contribute to the expression of future place cell sequences, which in turn contribute to the sequential neuronal patterns expressed post‐experience (i.e., replay). The relative contribution of preconfigured and of experience‐related factors to replay and to overall sequential activity during post‐run sleep is believed to be highly biased toward the recent run experience, despite never being tested directly. Here, we use multi‐neuronal sequence analysis unbiased by firing rate to compute and directly compare the contributions of internally generated and of recent experience‐driven factors to the sequential neuronal activity in post‐run sleep in naïve adult rats. We find that multi‐neuronal sequences during post‐run sleep are dominantly contributed by the pre‐run preconfigured patterns and to a much smaller extent by the place cell sequences and associated awake rest multi‐neuronal sequences experienced during de novo run session, which are weakly and similarly correlated with pre‐ and post‐run sleep multi‐neuronal sequences. These findings indicate a robust default internal organization of the hippocampal network into sequential neuronal ensembles that withstands a de novo spatial experience and suggest that integration of novel information during de novo experience leading to lasting changes in sequential network patterns is much more subtle than previously assumed.